2020
DOI: 10.1002/jwmg.21873
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Influences on Dall's Sheep Survival

Abstract: Understanding how species respond to environmental conditions can assist with conservation strategies and harvest management, especially in arctic and boreal regions that are experiencing rapid climate change. Although climatic influences on species distributions have been studied, broad‐scale effects of climate on survival are less well known. We examined the interactive effects of meteorological and remotely sensed environmental variables on survival of Dall's sheep (Ovis dalli dalli) lambs and adults by syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Furthermore, an index of green vegetation (NDVI) was positively, but not significantly selected by sheep during summer in LCNPP ( Table 3 ). Similar patterns were reported by van de Kerk et al [ 34 ] who found that maximum summer NDVI was associated with higher lamb survival and Roffler et al [ 38 ] who noted that Dall’s sheep selected intermediate values of NDVI during summer. Mountain sheep move to forage in areas with newly emerged green vegetation with high nutritional content [ 18 , 74 ], and the lack of a strong effect of NDVI on habitat selection during summer could be related to the presence of alpine dwarf evergreen scrub year round [ 73 ] and/or to tradeoffs associated with other ecological needs including security [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, an index of green vegetation (NDVI) was positively, but not significantly selected by sheep during summer in LCNPP ( Table 3 ). Similar patterns were reported by van de Kerk et al [ 34 ] who found that maximum summer NDVI was associated with higher lamb survival and Roffler et al [ 38 ] who noted that Dall’s sheep selected intermediate values of NDVI during summer. Mountain sheep move to forage in areas with newly emerged green vegetation with high nutritional content [ 18 , 74 ], and the lack of a strong effect of NDVI on habitat selection during summer could be related to the presence of alpine dwarf evergreen scrub year round [ 73 ] and/or to tradeoffs associated with other ecological needs including security [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Female sheep in LCNPP selected habitat with less snow cover and shallower snow depths during spring and winter, and warmer winters will reduce both of these factors, allowing more and longer access to forage [ 4 , 8 , 33 ]. However, changes in the composition and frequency of precipitation, such as rain-on-snow events and changes in temperature that lead to a higher frequency of freeze-thaw cycles, will increase the cost of movement by sheep and reduce access to forage [ 9 , 33 , 34 , 67 ]. Because of its location near the southern coast of Alaska, LCNPP could be particularly influenced by rain-on-snow events and a higher frequency of freeze-thaw cycles as opposed to regions in the interior of Alaska [ 9 , 34 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our dataset however does not include variables pertaining to the quality of vegetation available to ewes in the summer preceding or current to lambing. Both early [93] and more recent work [94] has connected metrics of summer forage quality with both lamb survival rates [93,94] and Dall's sheep productivity [93]. Also beyond the scope of the current study are the effects of interspecific relationships.…”
Section: Plos Onementioning
confidence: 92%
“…Also beyond the scope of the current study are the effects of interspecific relationships. The primary predators of Dall's sheep, coyote (Canis latrans) and golden eagles (Aquila chrysaetos), have been shown to account for less lamb mortality in summers with a high Normalized Difference Vegetation Index (NDVI) [94] and are likely to prey more on Dall's sheep during years with low snowshoe hare numbers [43,45]. To gain a more holistic understanding of Dall's sheep productivity and population dynamics, attention needs to be paid to a wide range of biotic and abiotic factors that are not considered here.…”
Section: Plos Onementioning
confidence: 99%